PERANAN AUDIT OPERASIONAL TERHADAP EFEKTIVITAS PEMBERIAN KREDIT (Studi Kasus pada PT. Pegadaian (Persero) Cabang Sukabumi) - Fany Savitri (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the role of the operational audit of the effectiveness of the provision of credit to the PT. Pegadaian (Persero) Branch Sukabumi, the variables used in this study is the operational audit and effectiveness of credit. The method used in this research is descriptive and associative. The scale used is ordinal scale. The population in this study were all employees at PT. Pegadaian (Persero) Branch Sukabumi. The data used are primary data and secondary data. Data were collected and analyzed using validity and reliability test, test the classical assumption of normality test, simple linear regression, hypothesis testing using t test, and test the coefficient of determination. Validity test results showed that all the questions for the independent variables and the dependent variable is declared invalid. Reliability test results unreliable. The result of the classical assumption of normality test showed that the role of the operational audit of the effectiveness of the credit granting normal distribution. The results of hypothesis testing (t-test) showed that t = 9.898> t table = 2.048. It can be concluded that the operational audits contribute significantly to the effectiveness of the loan. Results from test determination coefficient obtained the role of operational audit of the effectiveness of credit amounted to 77.8%. While the remaining 22.2% is influenced by other factors.